(untitled) (SAARC Journal of Agriculture, 2019)
The paper depicted the salient features of the socio-economic, farm and technological background and the existing problems of the peri-urban small and marginal dairy farmers of Chittagong Metro Area (CMA), Bangladesh. Data were collected using a pre-tested structured questionnaire. Snowball sampling method was used to gather socioeconomic, farm and technological data. Both descriptive statistics and mathematical analyses were used for analyzing the data. The study finds the peri-urban small and marginal dairy farmers are not fully dependent on dairy farming for income and young people are less interested in dairy farming as well. Better education status, less profitability, unfair and unstable price, etc. might be the reasons behind this circumstance. Though the farmers get lesser price for milk, the milk price is higher in urban market. Interestingly, 62.7%, 52.9% and 51.0% of the farmer families have smartphone, facebook and internet users respectively. Based on the findings, the study recommends that technology-based market linkage could be created by any government/non-government development partner between the cluster-based farmers’ group and the urban consumers for ensuring fair price for milk. SAARC J. Agri., 17(1): 77-91 (2019)